Investigating academic achievement in high school: an in-depth examination of top performing students - Jherwin P. Hermosa; Darwin D. Ofrin; Edilberto Z. Andal (Journal of Education and Learning (EduLearn), 2026)
This research aimed to identify the key qualities of high-achieving students to motivate and guide those not meeting their potential to adopt successful strategies and improve their academic results. Through the use of qualitative research methods and purposeful sampling, ten second-year college students from Laguna State Polytechnic University-San Pablo City Campus were selected for this study. Analysis of common themes identified ten key factors that contribute to academic success. These include developing strong reading habits, actively engaging in classroom instruction, effective time management, organized study materials, regular review of learned content, utilizing technology for learning enhancement, a supportive school environment, inspirational role models, and a strong support system involving parents and teachers. All individuals involved in a child’s education must understand and promote these attributes to optimize their learning experience, leading to tangible achievements in their academic performance. However, since this case study was conducted at a single school, it is not representative of all schools nationwide and cannot be generalized to the entire population. However, as it was conducted in a real-life setting, it is reasonable to draw pedagogical implications from these findings, as they offer insights into the characteristics of high-performing students.